Development of the Tumor-Specific Antigen-Derived Synthetic Peptides as Potential Candidates for Targeting Breast and Other Possible Human Carcinomas - Subhani M. Okarvi; Ibrahim AlJammaz (Molecules, 2019)
The human epidermal growth factor receptor 2 (HER2) represents one of the most studied tumor-associated antigens for cancer immunotherapy. The receptors for HER2 are overexpressed in various human cancers, such as breast and ovarian cancer. The relatively low expression of this antigen on normal tissues makes it a clinically useful molecular target for tumor imaging and targeted therapy. HER2 overexpression is correlated with aggressive tumor behavior and poor clinical outcomes. Thus, HER2 has become an important prognostic and predictive factor, as well as a potential molecular target. Due to the heterogeneity of breast cancer and possible discordance in HER2 status between primary tumors and distant metastases, assessment of HER2 expression by noninvasive imaging is important. Molecular imaging of HER2 expression may provide essential prognostic and predictive information concerning disseminated cancer and aid in the selection of an optimal therapy. Another tumor-specific antigen is MUC1, which is silent on normal tissues, but overexpressed in almost all human epithelial cell cancers, including >90% of human breast, ovarian, pancreatic, colorectal, lung, prostate, and gastric cancers and is a promising tumor antigen with diagnostic as well as the therapeutic potential of cancer. Radiolabeled small peptide ligands are attractive as probes for molecular imaging, as they reach and bind the target receptor efficiently and clear from blood and non-target organs faster than bulky antibodies. In this study, HER2 and MUC1-based peptides were synthesized and preclinically evaluated in an effort to develop peptide-based SPECT radiopharmaceuticals derived from tumor-associated antigens for the detection of breast cancer. Our findings demonstrate that the tumor antigen peptides radiolabeled efficiently with 99mTc and showed high metabolic stability in human plasma in vitro. The data from breast tumor cell binding confirmed the high affinity (in low nanomolar range) towards respective breast cancer cell lines. In healthy mice, 99mTc-labeled peptides displayed favorable pharmacokinetics, with high excretion by the renal system. In tumor xenografts nude mice models, good uptake by the SKBR3, MCF7, and T47D tumors were found, with good tumor-to-blood and tumor to muscle ratios. Additionally, tumor lesions can be seen in γ-camera imaging. Our data suggest that based on its ability to detect HER2- and MUC1-positive breast cancer cells in vivo, 99mTc-HER2 and 99mTc-MUC1-targeted peptides may be promising tumor imaging probes and warrant further investigation.